A Modified Side-to-Side Anastomosis Using a Circular Stapler Reduces Anastomotic Leakage in Colonic Surgery. (April 2020) - Luo, Wenjun; Qian, Chuan; Lu, Tingting; Zhang, Liuping; Sun, Meng; Li, Fugen; Xu, Zhengwen; Jia, Yingdong
Background . Anastomotic leakage (AL) remains one of the serious complications after colonic surgery. Method . A prospective interventional study to assess a modified technique of creating the ileocolic, colic-colic, and colorectal side-to-side anastomoses using a circular stapler. The primary endpoint was to evaluate the safety and efficacy of this technique in the reduction of AL. Computed tomography scan was performed when AL was clinically suspected. Result . One hundred and forty-five patients who underwent colonic resection between January 2015 and August 2018 were included. One patient underwent surgery for severe inflammatory bowel disease, and the others underwent surgery for colonic cancer. The procedures were open surgeries, including right hemicolectomy (n = 79 [54.5%]), left hemicolectomy (n = 29 [20%]), sigmoidectomy (n = 30 [20.7%]), and transverse colectomy (n = 7 [4.8%]). In 23 patients with ascending colonic obstruction, emergency right colectomy with primary anastomosis was performed. Two surgeons performed the operations (52.4% and 47.6%, respectively), and intraoperative blood loss was 50 to 100 mL. The operative time was 160 to 240 minutes. There was no mortality postoperatively, and 26 (17.9%) patients developed complications. One patient who underwent transverse colonic cancer resection developed a clinical AL (0.7%). After ileostomy, the patient was discharged with no other serious complication. The median of postoperative hospital stay was 8 days (range = 5-18 days). Conclusion . This modified technique is a safe and efficient method for anastomotic configuration in colonic surgery.